Upaya Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Matematika tentang Pecahan melalui Metode Problem Solving di Kelas IV/B SDN Cimanuk 1 - Rojudin Rojudin; Ratu Mauladaniyati (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
Efforts to improve the quality of education continue to be carried out systematically. This educational renewal is a conscious effort that is deliberately carried out with the aim of seriously improving educational practice but the current reality shows that in the field of education we still face problems, namely the low quality of output produced. Likewise in the learning process in class. Teachers often face students who have low learning motivation, which also affects their low learning achievement. Another fact also shows that the teaching methods of teachers in the classroom tend to be monotonous and do not vary. Based on this background, the researchers compiled this research with the aim of: 1) To determine the increase in mathematics learning outcomes about fractions through Problem Solving at SDN Cimanuk 1, Cimanuk District. 2) To improve teacher professionalism and performance. The subjects in this study were 24 grade IV students with details of 13 women and 11 women. The results of this study indicate an increase in student learning outcomes from each cycle, seen from the initial cycle only 13 students or 54.2% who completed learning, after the improvement in cycle I increased to 19 students or 79.2%, as well as the second cycle. significantly increased to 24 students or 100% who complete the study. This shows that Problem Solving can improve student learning outcomes in mathematics about fractions of class IV odd semester SDN Cimanuk 1, Cimanuk District, Pandeglang Regency